2016
DOI: 10.1038/srep26057
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mitochondrial Transformation into Human Cells

Abstract: Mitochondria can be incorporated into mammalian cells by simple co-incubation of isolated mitochondria with cells, without the need of transfection reagents or any other type of intervention. This phenomenon was termed mitochondrial transformation, and although it was discovered in 1982, currently little is known regarding its mechanism(s). Here we demonstrate that mitochondria can be transformed into recipient cells very quickly, and co-localize with endogenous mitochondria. The isolated mitochondria interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 53 publications
(82 reference statements)
6
93
0
1
Order By: Relevance
“…Our earlier experiments, and those of others, established that endocytosis of extracellular mitochondria was dependent on actin polymerization and that internalisation of these organelles resulted in long-term replenishment of mtDNA in HeLa cell-derived ρ 0 cells, which are otherwise devoid of mtDNA 9,11,14,2931 . Restoration of the ρ 0 mitochondrial genome through uptake of mitochondria isolated from HeLa cells led to enhancement of intracellular ATP levels and oxygen consumption rates 9 .…”
Section: Discussionmentioning
confidence: 52%
“…Our earlier experiments, and those of others, established that endocytosis of extracellular mitochondria was dependent on actin polymerization and that internalisation of these organelles resulted in long-term replenishment of mtDNA in HeLa cell-derived ρ 0 cells, which are otherwise devoid of mtDNA 9,11,14,2931 . Restoration of the ρ 0 mitochondrial genome through uptake of mitochondria isolated from HeLa cells led to enhancement of intracellular ATP levels and oxygen consumption rates 9 .…”
Section: Discussionmentioning
confidence: 52%
“…In fact, pre-treating cells with EIPA, a macropinocytosis inhibitor, impeded the mitochondria uptake in a dose-dependent manner whereas chlorpromazine, a clathrin-mediated endocytosis inhibitor, had no effect [98,100]. Mitochondrial transformation depends on the integrity of the outer mitochondrial membrane and the presence of intact fusogens that conduct effective mitochondrion-cell interactions [100,101]. For instance, D ıaz-Carballo and colleagues reported that mitochondria acquisition in chemo-resistant U87 RETO glioblastoma cells is syncytin-mediated.…”
Section: Transfer Of Free Mitochondriamentioning
confidence: 99%
“…They observed that, by simple co-incubation, chloramphenicol-(CAP s ) and efrapeptin-(EF s ) sensitive mammalian cells were able to incorporate mitochondria, purified beforehand from CAP r and EF r resistant cells [97]. Ever since, many cells have been reported to undergo mitochondrial transformation [55,[98][99][100][101][102]. This process is believed to occur via macropinocytosis.…”
Section: Transfer Of Free Mitochondriamentioning
confidence: 99%
“…The final Ca 2+ concentration in the dish is not measured, hence, it is unknown whether the conditions for mitochondrial transformation in cell culture prevent permeability transition pore activation. Internalization of functional mitochondria was demonstrated (15,16), most convincingly by the restoration of mitochondrial respiration in rho0 cells, mitochondria after resuspending them in high Ca 2+ physiological buffer, which the McCully group has not done.…”
Section: How Do Mitochondria Enter Cardiac Myocytes?mentioning
confidence: 99%